Ответ:
1) x = -6
2) x = 4
Пошаговое объяснение:
1) 7х+56=14
7x = 14 - 56
7x = -42
x = -42/7
x = -6
2) 8(х-2)-3х=4
8x - 16 - 3x = 4
5x = 4 + 16
5x = 20
x = 4
1) х = -6.
2) х = 4.
1) 7х + 56 = 14
7х = 14 - 56
7х = -42
х = -42/7
х = -6.
Проверка:
7*(-6) + 56 = 14
14 = 14.
2) 8(х - 2) - 3х = 4
8х - 16 - 3х = 4
8х - 3х = 4 + 16
5х = 20
х = 20/5
х = 4.
8*(4 - 2) - 3*4 = 4
4 = 4.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1) x = -6
2) x = 4
Пошаговое объяснение:
1) 7х+56=14
7x = 14 - 56
7x = -42
x = -42/7
x = -6
2) 8(х-2)-3х=4
8x - 16 - 3x = 4
5x = 4 + 16
5x = 20
x = 4
Ответ:
1) х = -6.
2) х = 4.
Пошаговое объяснение:
1) 7х + 56 = 14
7х = 14 - 56
7х = -42
х = -42/7
х = -6.
Проверка:
7*(-6) + 56 = 14
14 = 14.
2) 8(х - 2) - 3х = 4
8х - 16 - 3х = 4
8х - 3х = 4 + 16
5х = 20
х = 20/5
х = 4.
Проверка:
8*(4 - 2) - 3*4 = 4
4 = 4.